Enhancing Creative Agency in Poetry Translation: Integrating Project-Based Learning and Digital Mediation - Elissa Evawani Tambunan; Yusra Fadillah; Yulia Rizki Ramadhani; Elissa Evawani Tambunan; Yusra Fadillah (Universitas Negeri Malang, 2026)
Translation courses in EFL higher education often prioritize linguistic accuracy over creative expression, limiting students' agency and digital skills in poetry translation. This study aims to develop and evaluate a Project-Based Learning (PjBL) model integrated with digital media to enhance creativity among sixth-semester English Education students. Using a quasi-experimental mixed-methods design with 22 participants, pre- and post-intervention performance-based creativity tests assessed fluency, originality, flexibility, and elaboration; observation checklists tracked collaboration and engagement; and semi-structured interviews captured student perceptions. Quantitative data underwent paired-sample t-test analysis, while qualitative data received thematic analysis. Results revealed significant creativity gains (mean score rising from 60.9 to 79.2, p < 0.05), with originality improving most prominently; observations confirmed high digital tool use and teamwork; interviews highlighted boosted motivation and confidence. Integrating PjBL and digital media proves effective for fostering creative agency, digital literacy, and higher-order thinking in EFL translation pedagogy.